Peculiarities of Change in Immunological and Biochemical Indices in Organism of Rats with Experimental Allergic Encephalomyelitis - Goltsev, A. N.; Kozlova, Yu. A.; Babenko, N. N.; Ovsyannikov, S. E.; Nikitchenko, Yu. V. (Problems of Cryobiology and Cryomedicine, 2004)
The investigation results of the intensity of metabolic processes and the indices of immune status in the model of experimental allergic encephalomyelitis (EAE) of rats as the analogue of human multiple sclerosis (MS) are shown. The presence of correlations between studied indices is noted. The data obtained can be used in clinical practice for optimisation of the MS treatment method.